Cavity ringdown spectroscopy for the analysis of small liquid volumes - Vallance, C; Rushworth, C (Springer-Verlag Berlin Heidelberg, 2013)
Cavity-enhanced absorption techniques show considerable promise for applications in which a high detection sensitivity is required while maintaining a small probed volume of liquid sample. Conventional two-mirror cavity ringdown or cavity-enhanced absorption spectroscopy appears to provide a simple general 'benchtop' platform for measurements on flow cells and microfluidic chips with suitable optical properties, and recent progress in developing integrated cavities on-chip hints at the potential for future miniaturised self-contained microfluidic devices.